Misfolded alpha-synuclein detection by RT-QuIC in dementia with lewy bodies: a systematic review and meta-analysis - Peña-Bautista, Carmen; Kumar, Rakesh; Baquero, Miguel; Johansson, Jan; Cháfer-Pericás, Consuelo; Abelein, Axel; Ferreira, Daniel (Frontiers in Molecular Biosciences, 2023)
Dementia with Lewy Bodies (DLB) is the second most common cause of neurodegenerative dementia after Alzheimer’s disease (AD), but the field is still lacking a specific biomarker for its core pathology: alpha-synuclein (α-syn). Real-time quaking induced conversion (RT-QuIC) has recently emerged as a strong biomarker candidate to detect misfolded α-syn in DLB. However, the variability in the parameters of the technique and the heterogeneity of DLB patients make the reproducibility of the results difficult. Here, we provide an overview of the state-of-the-art research of α-syn RT-QuIC in DLB focused on: (1) the capacity of α-syn RT-QuIC to discriminate DLB from controls, Parkinson’s disease (PD) and AD; (2) the capacity of α-syn RT-QuIC to identify prodromal stages of DLB; and (3) the influence of co-pathologies on α-syn RT-QuIC’s performance. We also assessed the influence of different factors, such as technical conditions (e.g. temperature, pH, shaking-rest cycles), sample type, and clinical diagnosis versus autopsy confirmation. Our meta-analysis shows that α-syn RT-QuIC reaches very high diagnostic performance in discriminating DLB from both controls (pooled sensitivity and specificity of 0.94 and 0.96, respectively) and AD (pooled sensitivity and specificity of 0.95 and 0.88) and is promising for prodromal phases of DLB. However, the performance of α-syn RT-QuIC to discriminate DLB from PD is currently low due to low specificity (pooled sensitivity and specificity of 0.94 and 0.11). Our analysis showed that α-syn RT-QuIC’s performance is not substantially influenced by sample type or clinical diagnosis versus autopsy confirmation. Co-pathologies did not influence the performance of α-syn RT-QuIC, but the number of such studies is currently limited. We observed technical variability across published articles. However, we could not find a clear effect of technical variability on the reported results. We conclude that there is currently enough evidence to test misfolded α-syn by RT-QuIC for clinical use. We anticipate that harmonization of protocols across centres and advances in standardization will facilitate the clinical establishment of misfolded α-syn detection by RT-QuIC.